2016
DOI: 10.1080/15685551.2016.1259839
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different amounts of drug microspheres on the vivo and vitro performance of the PLGA/β-TCP scaffold

Abstract: OIC-A006 (BMPs osteogenesis compounds), can stimulate bone marrow mesenchymal stem cells ALP, OPN, OC, Cbfal expression. To stimulate new bone formation in the body. We postulate different amounts of drug microspheres on the PLGA/β-CPT scaffold can produce the effects on performance and sustained release characteristics. In this paper, through adding different amount of carrier drug microsphere, three concentrations scaffolds which are 12.5, 18.75 and 25 μmol/L are prepared by adding different amounts of drug-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Besides conventional TCP-based implants, the in vivo bone forming potential of RALA complexed α-TCP nanoparticle delivery has been investigated with a promising outcome . Several other studies on TCP-based implants can also be found in the recent literature. These studies are the evidence of the ability of TCP toward osteoinduction, in vivo.…”
Section: Insight Into Functional and Biological Propertiesmentioning
confidence: 99%
“…Besides conventional TCP-based implants, the in vivo bone forming potential of RALA complexed α-TCP nanoparticle delivery has been investigated with a promising outcome . Several other studies on TCP-based implants can also be found in the recent literature. These studies are the evidence of the ability of TCP toward osteoinduction, in vivo.…”
Section: Insight Into Functional and Biological Propertiesmentioning
confidence: 99%
“…Copyright 2019 by BioMed Central Ltd. (B-b) Adapted with permission from ref ( He et al, 2021 ). Copyright 2020 by Elsevier Ltd. (B-c) Adapted with permission from ref ( Lin et al, 2016 ). Copyright 2016 by Taylor and Francis Group.…”
Section: Different Types Of Scaffolds In Osteochondral Tissue Engineeringmentioning
confidence: 99%
“…Mohan N et al fabricated PLGA-CS-NaHCO 3 as chondrogenic MSs and PLGA-β-TCP as osteogenic MSs to produce a gradient scaffold ( Mohan et al, 2015 ). Recently, various studies have reported the utility of drug or gene delivery MSs for effective osteochondral tissue regeneration ( Lin et al, 2016 ; Madry et al, 2020 ; He et al, 2021 ).…”
Section: Different Types Of Scaffolds In Osteochondral Tissue Engineeringmentioning
confidence: 99%